The Influence of Online Games on the Learning Concentration of Students at SMPN 1 Madapangga and the Level of Anxiety of Students' Parents - M. Sya'aban Yudha Satria; Ardi Rahmawan; Lisda Ramdhani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Online games currently affect various aspects of human life, including health, psychology, and concentration of students at SMPN 1 Madapangga, and cause anxiety among parents. This study is quantitative and qualitative, using descriptive qualitative methods. The population of this study was 554 students and 70 parents. The sample used was 50 students from grades VII, VIII, and IX, and 50 parents. The sampling technique used was non-probability sampling in the form of purposive sampling. Data collection techniques used included observation, interviews, documentation, and Likert scale questionnaires. Data analysis techniques used included interactive/model data analysis techniques and Spearman test data analysis techniques. The results of this study, namely from 25 male students at SMPN 1 Madapangga, who experienced low concentration levels were 10 students (20%), 7 students with moderate concentration levels (14%), and 6 students with high concentration levels (12%). Meanwhile, of the 25 female students, 5 experienced low concentration levels (10%), 12 experienced moderate concentration levels (24%), and 10 experienced high concentration levels (20%). This means that more male students experienced a decrease in learning concentration compared to female students. However, in terms of anxiety levels, female parents experienced higher levels of anxiety than male parents. There were 32 female parents who experienced mild, moderate, and severe anxiety with a percentage of 64%. Meanwhile, 18 male parents experienced mild, moderate, and severe anxiety with a percentage of 36%.